Influence of the solar cycle on the general circulation of the stratosphere and upper troposphere - Salby, M. L.; Callaghan, P. F. (Space Science Reviews, 2006)
The record of dynamical structure reveals a systematic variation that operates coherently with the 11-yr variation of UV irradiance. Involving periods shorter than 5 years, the systematic variation reflects the influence of the QBO on the polar-night vortex. It has the same basic structure as interannual changes associated with the residual mean circulation of the stratosphere. A signature of the solar cycle also appears in the direct correlation to solar flux, as recovered through regression of the entire monthly record. That signature, however, is sharply enhanced around solstice, when the residual circulation is active, and during extremal phases of the QBO. In the tropics, the solar signature follows, throughout the year, from a decadal modulation in the frequency of the QBO. The modulation is manifested to either side of the QBO's mean frequency, in two spectral peaks where the QBO dwells: one at (24 months) -1 , reflecting a Biennial Oscillation (BO), and another at (36 months) -1 . Intrinsic to the QBO, those peaks are separated from its mean frequency by ∼11 years -1 .Through the QBO's residual circulation, the decadal modulation introduces anomalies in the subtropics, with symmetry about the equator. Accompanying anomalous temperature in the subtropics is a stronger signature over the winter pole. Discovered by Labitzke and van Loon 1988, that solar signature reflects anomalous downwelling of the Brewer-Dobson circulation. It is shown to follow through the BO, which is intrinsic to the QBO and its modulation of the polar-night vortex.